Meta-Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Stres Akademik Pada Mahasiswa - Zega, Christine Jenny Puspita; Zega, Frendy Premier (CV. SINAR HOWUHOWU, 2025)
This meta-analysis examines the factors influencing academic stress levels among Indonesian university students. Through a systematic analysis of 63 studies published between 2014-2024, encompassing 31,847 students from various regions in Indonesia, we investigated the multidimensional nature of academic stress and its contributing factors. Using comprehensive statistical methods including random-effects modeling and moderator analysis, we identified significant correlations between academic stress and various predictors, with academic workload (r = 0.56, p < 0.001) and environmental factors (r = 0.48, p < 0.001) emerging as the strongest contributors. The findings provide crucial insights for developing targeted interventions and support systems within Indonesian higher education institutions.